Theoretical foundations of multimedia - Tannenbaum, Robert S. (Robert Sher) (New York : Computer Science Press, 1998)
History and uses of multimedia. Light and sound, seeing and listening. Hardware that enables multimedia. Software that enables multimedia. Communication theory and developments underlying the use of multimedia...
Keywords: Computer; Multimedia systems; Multimedia systems